2011
DOI: 10.1111/j.1600-0625.2011.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial mapping by imaging mass spectrometry offers advancements for rapid definition of human skin proteomic signatures

Abstract: Investigations of the human skin proteome by classical analytical procedures have not addressed spatial molecular distributions in whole skin biopsies. The aim of this study was to develop methods for detection of protein signatures and their spatial disposition in human skin using advanced molecular imaging technology based on mass spectrometry technologies. This technology allows for the generation of protein images at specific molecular weight values without the use of antibody while maintaining tissue arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 62 publications
(74 reference statements)
1
33
2
Order By: Relevance
“…For example, calgizzarin (ion at m/z 11651) is mainly distributed close to the epidermis without differences between control and PXE specimens. In the case of thymosin beta-4 (TYB-4) (m/z 4965), this protein is density mapped in the papillary dermis adjacent to the mineralized region in both PXE samples, whereas it is localized within the whole dermis in controls, as previously described in normal healthy skin [15]. By contrast, the cleaved form of TYB-4 (m/z 4748) is always present in the papillary dermis, whereas it is absent in the control reticular dermis and in the mineralized regions.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…For example, calgizzarin (ion at m/z 11651) is mainly distributed close to the epidermis without differences between control and PXE specimens. In the case of thymosin beta-4 (TYB-4) (m/z 4965), this protein is density mapped in the papillary dermis adjacent to the mineralized region in both PXE samples, whereas it is localized within the whole dermis in controls, as previously described in normal healthy skin [15]. By contrast, the cleaved form of TYB-4 (m/z 4748) is always present in the papillary dermis, whereas it is absent in the control reticular dermis and in the mineralized regions.…”
Section: Resultsmentioning
confidence: 64%
“…We have recently optimized techniques for IMS analysis of human skin and have used only minor modifications of our published procedures [15, 16]. Fresh frozen human skin blocks (approximately 1cm 3 ) were sectioned at 8 μm using a cryostat (CM 3050 S, Leica Microsystems GmbH, Wetzlar, Germany) set at -22 °C.…”
Section: Methodsmentioning
confidence: 99%
“…All keratins can be divided into two types—type I acidic keratins (K9‐K20; 17q12‐q21) and type II basic keratins (K1‐K8; 12q11‐q13)—depending on the level of cell differentiation, growth environment, and disease state . KRT1 and KRT10 are highly characteristic of the outer, highly differentiated epidermal strata, and studies have found that the levels of KRT1 and KRT10 were significantly decreased in patients with hyperkeratotic skin diseases, such as keratinopathic ichthyoses (KPIs) . The levels of KRT5 and KRT14 expressed in the basal cell layer were normal, and KRT14 was restricted to the undifferentiated epidermal stratum .…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been successfully applied using both fresh frozen and formalin-fixed tissues. 3140 …”
Section: Basic Concepts Of Maldi Imaging Mass Spectrometrymentioning
confidence: 99%